Effect of COVID‐19 on health system integration in the Netherlands: a mixed‐methods study. Issue 3 (1st May 2021) - Minderhout, Rosa Naomi; Baksteen, Martine C.; Numans, Mattijs E.; Bruijnzeels, Marc A.; Vos, Hedwig M.M.
Abstract: Objectives: Overcrowding in acute care services gives rise to major problems, such as reduced accessibility and delay in treatment. In order to be able to continue providing high‐quality health care, it is important that organizations are well integrated at all organizational levels. The objective of this study was to to gain an understanding in which extent cooperation within an urban acute care network in the Netherlands (The Hague) improved because of the COVID‐19 crisis. Methods: Exploratory mixed‐methods questionnaire and qualitative interview study. Semistructured interviews with stakeholders in the acute care network at micro (n = 10), meso (n = 9), and macro (n = 3) levels of organization. Thematic analysis took place along the lines of the 6 dimensions of the Rainbow Model of Integrated Care. Results: In this study we identified themes that may act as barriers or facilitators to cooperation: communication, interaction, trust, leadership, interests, distribution of care, and funding. During the crisis many facilitators were identified at clinical, professional, and system level such as clear agreements about work processes, trust in each other's work, and different stakeholders growing closer together. However, at an organizational and communicative level there were many barriers such as interference in each other's work and a lack of clear policies. Conclusion: The driving force behind all changes in integration of acute care organizations in an urban context during the COVID‐19 crisis seemed to be a great sense of urgency to cooperate in the shared interest of providing the best patient care. We recommend shifting the postcrisis focus from overcoming the crisis to overcoming cooperative challenges.